Carbon monoxide emission lines reveal an inverted atmosphere in the ultra hot Jupiter WASP-33 b consistent with an eastward hot spot. Issue 2 (17th April 2023) - van Sluijs, Lennart; Birkby, Jayne L; Lothringer, Joshua; Lee, Elspeth K H; Crossfield, Ian J M; Parmentier, Vivien; Brogi, Matteo; Kulesa, Craig; McCarthy, Don; Charbonneau, David
ABSTRACT: We report the first detection of CO emission at high spectral resolution in the day-side infrared thermal spectrum of an exoplanet. These emission lines, found in the atmosphere of the transiting ultra hot Jupiter (UHJ) WASP-33 b, provide unambiguous evidence of its thermal inversion. Using spectra from the MMT Exoplanet Atmosphere Survey (MEASURE, R ∼ 15 000), covering pre- and post-eclipse phases, we cross-correlate with 1D PHOENIX spectral templates to detect CO at S/N = 7.9 (v_sys=0.15^+0.64_-0.65 km s −1, K_p=229.5^+1.1_-1.0 km s −1 ). Moreover, using cross-correlation-to-log-likelihood mapping, we find that the scaling parameter which controls the spectral line contrast changes with phase. We thus use the general circulation model SPARC/MITgcm post-processed by the 3D gCMCRT radiative transfer code to interpret this variation, finding it consistent with an eastward-shifted hot spot. Pre-eclipse, when the hot spot faces Earth, the thermal profiles are shallower leading to smaller line contrast despite greater overall flux. Post-eclipse, the western part of the day-side faces Earth and has much steeper thermal profiles, leading to larger line contrast despite less overall flux. This demonstrates that within the log-likelihood framework, even relatively moderate resolution spectra can be used to understand the 3D nature of close-in exoplanets, and that resolution can be traded for photon-collecting power when the induced Doppler-shift is sufficiently large. We highlight CO as a good probe of UHJ thermal structure and dynamics that does not suffer from stellar activity, unlike species that are also present in the host star e.g. iron lines.